Portability of Interfaces in Healthcare EAI Environments - Linecker, Severin; Wöss, Wolfram (Computing and Informatics, 2022)
Enterprise Application Integration (EAI) and HL7 (Health Level Seven) messaging are well established technologies in healthcare environments. Due to the age and longevity of HL7 standards (especially HL7 V2.x) and their widespread use, many interfaces outlive the middleware on which they run and must be ported to new systems. This often requires the entire code of the interface to be rewritten, which is associated with great effort and costs. This paper shows a generic EAI framework based on configuration and dependency injection for implementing reusable interfaces upfront and the results when applied to a real production EAI environment of an Austrian healthcare provider.